THE IMPACTS OF OUTCOME-BASED EDUCATION FOR EFL LEARNERS’ LEARNING AUTONOMY IN THE INTRODUCTION TO EDUCATION CLASS - Kristian Florensio Wijaya (STKIP Siliwangi, 2020)
To enable all EFL learners to engage in teacher-course experiences to be high-quality educators in the future, outcome-based education needs to be implemented by all lecturers in charge of improving the future national educational systems through hands-on, enjoyable, and cooperative learning experiences. Therefore, outcome-based education had been assumed as one of the best answers to rejuvenate the whole educational policies nowadays since the learners will be able to engage more proactively in portraying their status as future educators through mutual cognitive and affective engagement. This study employed a qualitative method to investigate whether outcome-based education had successfully promoted learning autonomy for EFL learners engaging in the introduction to education class. Furthermore, two researcher instruments were also utilized to obtain a higher degree of trustworthiness in this study namely classroom observation and classroom survey. In accord with the gathered data, the findings suggest all EFL lecturers teaching in teacher-course experiences to apply outcome-based education fully to promote a higher degree of enjoyment in learning, engage all learners to be more highly participative in disseminating a wide array of knowledge, and raise more intriguing awareness for the lecturers to be more self-evaluative on their applied teaching-learning practices. Keywords: outcome-based education, EFL learners’ learning autonomy, introduction to education class